Sistem Pendukung Keputusan Pemilihan Kampus Menggunakan Metode Multi Factor Evaluation Process - Sri Andriyani; Ryci Rahmatil Fiska (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Choosing a campus is a crucial decision for prospective students because it influences their learning and self-development process. With 13 campuses available in Bengkalis and Pekanbaru, prospective students often face difficulties in determining the right choice for their preferences and needs. Therefore, a recommendation system is needed that can help make decisions quickly and accurately without complicated searches. This study aims to design a campus selection recommendation system using the Multi Factor Evaluation Process (MFEP) method, which considers six main factors: tuition fees, majors, scholarships, type of college, admission pathways, and accreditation. This method involves weighting and evaluation to produce more accurate recommendations. The system development uses the Rapid Application Development (RAD) method, enabling a fast and iterative process by involving users at every stage. The result of this system is a recommendation system that can help prospective students determine the best campus according to the selected criteria, thus facilitating the decision-making process efficiently. The result of this system is a recommendation system that can help prospective students determine the best campus according to the selected criteria, thus facilitating the decision-making process efficiently.